After Callimachus : Poems - Burt, Stephanie (The Lockert Library of Poetry in Translation Ser, 2020)
Cover -- Title Page -- Copyright Page -- Contents -- Foreword by Mark Payne -- Imitator's Note -- 1 -- So reactionaries and radicals complain (Aetia, book 1, frag. 1: proem) -- This is a story with a happy ending (Aetia, book 3, frag. 67-75) -- That island feast (Galatea, frag. 378) -- Apollo has come to our house party, and Aphrodite (Lyric, frag. 227) -- Caro, you didn't seem to experience more (Epigram 62) -- Sleep, Conopion, sleep (Epigram 64) -- Zeus (I read here) once made love for three hundred years (Aetia, book 2, frag. 48) -- It's easier to explain if we use Mr. Spock (Epigram 43) -- The lord of the gods gets crushes on people too (Epigram 53) -- Honestly I don't know (Hecale, frag. 274) -- I hate to say it, Lee, but you look awful (Epigram 32) -- You were already in pain (Epigram 44) -- Warm ashes may flare up when stirred (Epigram 45) -- Don't worry, you (Hecale, frag. 256) -- There are so many versions of Aphrodite (Iamb 10, frag. 200a) -- Once they decided to make a home together (Epigram 27) -- The shepherds I know tell stories for one another (Epigram 24) -- When you can't be with somebody you want to be with-(Epigram 33) -- It's hard work making people fall in love (Epigram 39) -- Snakes stand for danger, but also for things intertwining (Aetia, book 4, frag. 101a) -- Snakes stand for danger, but also for things intertwining (Aetia, book 4, frag. 101b) -- Fun fact: long ago, in the age of myth (Epigram 47) -- 2 -- The fuckers renamed an airport for a tyrant (Epigram 8) -- It hurts to be poor. It hurts more (Hecale, frag. 275) -- Choose me, Athena, defender (frag. 556, 638, 644) -- Berenice, rightful governor (frag. 388) -- All the Greek cities have seen their refugees (Aetia, book 2, frag. 44-51) -- The way a word like sanction, or inflammable (Aetia, book 4, frag. 90).